Rosemary essential oil in the control of diseases and induction of resistance in grapevine - Maia, Aline José; Schwan-Estada, Kátia Regina Freitas; Faria, Cacilda Márcia Duarte Rios; Oliveira, Juliana Santos Batista; Jardinetti, Virlene Amaral; Batista, Bruno Neves (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to determine the chemical qualities of rosemary essential oil and its effect on productivity, on the control of leaf spot and mildew, and on the induction of resistance in 'Isabel' grapevine. The experiment was carried out in a commercial vineyard, in two consecutive cycles. The treatments consisted of the essential oil doses: 0, 500, 1,000, 2,000, and 4,000 µL L‑1, besides the Tween 80%, bordeaux mixture, acibenzolar‑S‑methyl, and mancozeb treatments. Severity of leaf blight and mildew, the activity of chitinase and catalase enzymes, and mass and number of clusters and chemical characteristics of grapes were evaluated. There was a quadratic effect as affected by the doses of essential rosemary oil, for severity of leaf spot and mildew in grapevine, in both cycles, with results similar to those of bordeaux mixture, acibenzolar‑S‑methyl, and mancozeb. There was also an increase in the number and mass of clusters, as well as in productivity. The essential oil did not affect the chemical characteristics of grapes. An increase in the activity of the chitinase enzyme and a decrease in the catalase activity were observed in leaves. Essential oil at the doses of 500, 1,000, and 2,000 µL L‑1 is an alternative for the control of diseases in 'Isabel' grapevine.